HAK PASIEN ATAS PRIVASI DATA MEDIS: TINJAUAN LITERATUR DAN EVALUASI KEBIJAKAN - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. ADIBA AISHA AMIRA, 2025)
Patients' rights to privacy and confidentiality of medical data are fundamental aspects of the healthcare system, especially in the era of digitalisation and information technology utilisation. This study aims to examine the protection of patients' privacy rights regarding medical data through a literature review and policy evaluation in Indonesia. The method used is literature research by analysing national regulations, such as the Personal Data Protection Law, the Health Law, and the Minister of Health Regulation on Medical Records, and comparing them with international standards. The results of the study indicate that although the legal framework in Indonesia has explicitly recognised and regulated patient privacy rights, implementation in the field still faces challenges such as weak data security infrastructure, low privacy literacy among health workers and patients, and suboptimal supervision and law enforcement. This study recommends the need to strengthen policies, enhance human resource capacity, and update information technology infrastructure to ensure effective protection of patient privacy rights and support public trust in healthcare services.